Teaching styles and principles for organizing students' physical education, sports wellness classes - Satimov Azamjon Ikromovich; Ortiqov Umidjon Godoyberdiyevich; Ortiqov Sirojiddin Xoldorjon o'g'li (Genius Journals, 2022)
This article provides information about the teaching methods and principles of organizing physical education, sports health activities, the purpose and content, the formation of materials, and the types of discipline.
Keywords: Students; physical education; well-being; pedagogical system